La competitividad organizacional como factor crítico en la gestión del talento humano (2019)
The present document aims to detail the relationship between the good use of human talent and organizational competitiveness taking into account the increasing globalization that has been growing during the last decades. Globalization has created a difficulty for industries facing the idea of remaining competitive with other companies, since not only are they competing with companies located in the same town, city or country, but they are also competing against the companies worldwide.